Acute effect of cluster and traditional set configurations on myokines associated with hypertrophy - Oliver, J. M.; Jenke, S. C.; Mata, J. D.; Kreutzer, A.; Jones, M. T. (International Journal of Sports Medicine, 2016)
This study compared the acute cytokine response, and kinetic and kinematic profile following back squat exercise in resistance-trained men. In a randomized, cross-over design, 10 resistance-trained men (27±4 y, 1.80±0.07 m, 82.8±6.7 kg, 16.3±3.5% fat) performed the back squat exercise using traditional and cluster set configurations. Kinetic and kinematic data were sampled throughout each condition. Venous blood was sampled prior, immediately post, 30 min, 60 min, 24 h, and 48 h post-exercise for plasma interleukin-6 (IL-6) and interleukin-15 (IL-15). Cluster sets allowed for greater mean power (mean difference, 110?W; 90% confidence interval, ±63?W; benefit odds, 41 447:1), driven by higher overall mean velocities (0.053 m·s-1; 0.039 m·s-1; 3 105:1) as evidenced by the lack of clear contrasts for mean force. IL-15 increased post-exercise in both conditions, but increased at 24 h (0.13 pg·mL-1; ±0.11 pg·mL-1; 486:1) and 48 h (0.12 pg·mL-1; ±0.10 pg·mL-1; 667:1) in traditional sets only. IL-6 increased similarly in both conditions, post-exercise through 60 min post. Cluster set configurations allow for greater mean power, attributed to higher velocities. Despite a similar response of IL-6, traditional set configuration may provide a greater stimulus for hypertrophy as evidenced by a secondary increase in IL-15.